2020
DOI: 10.21203/rs.3.rs-50645/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resistin-like Molecule β Acts as a Mitogenic Factor in Hypoxic Pulmonary Hypertension via the Ca2+-dependent PI3K/Akt/mTOR and PKC/MAPK Signaling Pathways

Abstract: BACKGROUND: Pulmonary arterial smooth muscle cell (PASMC) proliferation plays a crucial role in hypoxia-induced pulmonary hypertension (HPH). Previous studies have found that resistin-like molecule β (RELM-β) is upregulated de novo in response to hypoxia in cultured human PASMCs (hPASMCs). RELM-β has been reported to promote hPASMC proliferation and is involved in pulmonary vascular remodeling in patients with PAH. However, the expression pattern, effects, and mechanisms of action of RELM-β in HPH remain uncle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…PI3K/AKT plays a vital role in the regulation of cellular functions, including cell metabolism, growth, proliferation, survival, transcription, and protein synthesis [28]. Activation of the PI3K/AKT pathway promoted proliferation and migration of PASMCs, which is a wellrecognized characteristic of PAH [29][30][31][32]. Decrease of CacyBP/SIP effectively increased the phosphorylation levels of PI3K and AKT, resulting in a change in the phenotypic switch of PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT plays a vital role in the regulation of cellular functions, including cell metabolism, growth, proliferation, survival, transcription, and protein synthesis [28]. Activation of the PI3K/AKT pathway promoted proliferation and migration of PASMCs, which is a wellrecognized characteristic of PAH [29][30][31][32]. Decrease of CacyBP/SIP effectively increased the phosphorylation levels of PI3K and AKT, resulting in a change in the phenotypic switch of PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The AKT signalling pathway is a classic pathway that modulates PASMC dysfunction. Several studies have reported that the activation of AKT promotes phenotypic switch, proliferation, and migration of PASMCs, thus intensifying pulmonary vascular remodelling in PAH 25–27 . In addition, it has been demonstrated that SYN enhances the proliferation of glioblastoma cells via activation of the AKT signalling pathway 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that AKT signalling participates in the modulation of the phenotypic switch, proliferation, and migration of PASMCs in PAH. [25][26][27] In addition, Pitre et al showed that SYN positively promotes glioblastoma cell proliferation by promoting AKT activation. 17…”
Section: Syn Enhanced Hpasmc Phenotypic Switch Via Akt Signalling Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in cytosolic-free Ca 2+ and a decrease in mitochondrial Ca 2+ concentrations promote pulmonary vasoconstriction and PASMC proliferation through activation of PI3K/Akt/mTOR and MAPK pathways. 5,6 One of the important regulators of Ca 2+ homeostasis is a store-operated Ca 2+ channel, which mediates store-operated Ca 2+ entry. Store-operated Ca 2+ channel consists of the Ca 2+ channels Orai1-3 and, in part, transient receptor potential canonical channels, which are activated by stromal interacting molecules (STIM) in response to G-protein coupled receptors/PLC (phospholipase C)-induced endoplasmic reticulum-sarcoplasmic reticulum (SR) Ca 2+ store depletion.…”
Section: Article See P E102mentioning
confidence: 99%